Electronic structure and performance analysis of a pentagraphene based thermoelectric generator - Mulgeta Girma; Tadesse Lemma Wakjira; Kedir Hussien; Kumneger Tadele; Seyfan Kelil (AIP Advances, 2025)
This study investigated the potential of pentagraphene (PG) as a high-performance thermoelectric material for energy conversion applications. Electronic structure calculations revealed that PG is an indirect bandgap semiconductor with a bandgap energy of 2.11 eV and exhibits anisotropic dielectric and plasmon properties. The phonon dispersion calculation shows that the material is dynamically stable under small perturbations. Furthermore, compared with graphene, PG has a lower phononic thermal conductivity. Thermoelectric property calculations show that PG has a significantly higher figure of merit (ZT) of 0.15 at 300 K than graphene, with a ZT of 0.009. Moreover, the ZT of PG increases with temperature, reaching 0.52 at 900 K. Simulations of a PG-based thermoelectric generator (TEG) demonstrate an efficiency of 7% at a heat source temperature of 900 K. This finding suggests that PG possesses thermoelectric properties superior to those of graphene and holds significant potential for the development of more efficient and practical TEGs, particularly for applications requiring moderate temperatures.